"Red" Banks : The Contribution of Chinese Banks to the Economic Rise of China (1980-2020) - Song, Chenzhu (Social Sciences E-Books Online, Collection 2026., 2026)
Have you ever wondered how China's banking sector powered the world's most dramatic economic transformation? This book opens the vault, revealing how policy banks, state-owned giants, and daring joint-stock institutions fueled China's rise from 1980 to 2020. You'll explore unpublished financial records and financed reforms to Belt and Road mega-projects. How did China's banks sidestep the pitfalls of Western systems? What made their approach to infrastructure and manufacturing uniquely explosive? This study bridges gaps in global finance research, challenging conventional narratives and exposing the symbiotic relationship between state strategy and real economic growth.